2010
DOI: 10.1155/2010/737425
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Microbiology of the Female Reproductive Tract and the Causes of Premature Birth

Abstract: Data derived from molecular microbiological investigations of the human vagina have led to the discovery of resident bacterial communities that exhibit marked differences in terms of species composition. All undergo dynamic changes that are likely due to intrinsic host and behavioral factors. Similar types of bacteria have been found in both amniotic fluid and the vagina, suggesting a potential route of colonization. Given that not all of the species involved in intrauterine infections are readily cultivated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 82 publications
2
60
0
1
Order By: Relevance
“…Reads classified to the genus Gardnerella appeared to be undersampled from human samples (and possibly from NHP samples too) in this study, compared with previously published reports (Kim et al, 2009;Ravel et al, 2013). This may be attributed to not including the primer cocktail (27F-YM þ 3), as described in Frank et al, 2008. Recent studies (Zhou et al, 2010;Ravel et al, 2011;Ravel et al, 2013) have revealed Lactobacillus spp. in low abundance in the vaginal tract of a subpopulation of apparently healthy women with high Nugent scores, who have been categorized as 'asymptomatic BV' (ABV) in contrast to 'symptomatic BV' (SBV) subjects.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…Reads classified to the genus Gardnerella appeared to be undersampled from human samples (and possibly from NHP samples too) in this study, compared with previously published reports (Kim et al, 2009;Ravel et al, 2013). This may be attributed to not including the primer cocktail (27F-YM þ 3), as described in Frank et al, 2008. Recent studies (Zhou et al, 2010;Ravel et al, 2011;Ravel et al, 2013) have revealed Lactobacillus spp. in low abundance in the vaginal tract of a subpopulation of apparently healthy women with high Nugent scores, who have been categorized as 'asymptomatic BV' (ABV) in contrast to 'symptomatic BV' (SBV) subjects.…”
Section: Resultsmentioning
confidence: 47%
“…Of particular note, the relative abundances of lactobacilli were significantly lower in NHPs, whereas the majority of the human female populations have Lactobacillus as the dominant vaginal bacteria (60-93%, depending on the ethnicity (Zhou et al, 2010;Ravel et al, 2011)). Chimpanzees, the closest human relatives, had o3.5% lactobacilli.…”
Section: Resultsmentioning
confidence: 99%
“…Pregnant women who are colonized with GBS might develop infections of the urinary tract, bacteremia, chorioamnionitis, and postpartum endometritis 23,47,48 , thus increasing the risk of PTD, PPROM and perinatal transmission [49][50][51] , resulting in neonatal sepsis and meningitis 45,52,53 . A prevalence of 7 -25% GBS colonization in AV has been reported in women between 35 and 37 weeks of gestation 54 , with intrauterine infection associated with the ability of GBS to ascend from the lower genital tract and colonize the upper genital tract [54][55][56] . In the newborn, GBS infection may be congenital or acquired 22,57 and remains the foremost cause of neonatal mortality and morbidity in the world despite a recent decline in occurrence 48,52,58,59 .…”
Section: Group B Streptococci (Gbs)mentioning
confidence: 99%
“…3 Intrauterine infection is implicated in stillbirth 4 and is associated with 25% to 40% of preterm births. 5 Sexually transmitted infections and reproductive tract infections (STIs/RTIs) 6 and malaria 7 are associated with adverse birth outcomes, but both may be mitigated with preventive or presumptive treatment or by repeated screening and treatment throughout the antenatal period. The extent to which either approach may be beneficial depends on the underlying prevalence of STIs/RTIs and malaria in pregnancy.…”
mentioning
confidence: 99%